C-5d= -16

3c+2d= -14

Thank you for the opportunity to help you with your question!

To solve this problem, you need to solve for one variable in one equation, then substitute that variable into the other equation:

1. Solve for c in the first equation:

c-5d=-16

c=5d-16

2. Plug c into the second equation, then solve for d:

3c+2d=-14

3(5d-16)+2d=-14

15d-48+2d=-14

17d=34

d=2

3. Now plug d into either equation to solve for c:

c-5*2=-16

c-10=-16

c=-6

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up